A Blockchain-based Reputation System for Trust Management in Collaborative Multi-Stakeholder Settings - Miranda, Lívia Maria Bettini de; Garcia, Rodrigo Dutra; Ueyama, Jo; Ramachandran, Gowri; Guerrini, Fábio Müller (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain), 2024)
Organizations collaborate in industrial networks to share business risks, innovate, and deliver value-added products and services, relying on trust management. However, mistrust among stakeholders arises due to a lack of information transparency, coordination issues, and incentive misalignment. To overcome this problem, this work proposes a decentralized reputation system based on blockchain, smart contracts, and tokenization. Particularly, we address the problem of selecting partners for multi-stakeholder production through their token-based reputation. Our proof-of-concept evaluation results show that the proposed system is agnostic for Ethereum Virtual Machine-based (EVM) blockchains with low computational overhead.